A RAPID BIRD SURVEY TO CONSERVATION AREA OF INDUSTRIAL ACACIA TIMBER PLANTATION, SOUTH SUMATRA PROVINCE; WITH COMPARISON TO THREE DIFFERENT METHODS - Iqbal, Muhammad; Yustian, Indra; Setiawan, Doni; Saputra, Rio Firman; Prasetyo, Catur Yuono; Fadli, Dede (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2016)
A rapid bird survey was done in a small conservation area of industrial timber concession of PT BMH (Bumi Mekar Hijau), namely KPPN (Kawasan Pelestarian Plasma Nutfah), South Sumatra Province. The area has 448 ha, dominated by degraded secondary swamp forest surrounded by Acacia plantation. Three survey methods were applied to assess bird diversity in this area: transect line, mist-netting and audio-visual station recording. A total of 36 species was recorded during survey. Among three methods applied, transect line is the most effective method to detect more bird species (29 species), followed by audio-visual station recording (26 species) and mist-netting (three species). There are eight species which protected by Indonesian law and two birds are listed as Near Threatened (NT) by International Union for Conservation of Nature or IUCN. Although number of species birds recorded are not significance, but this area still support habitat for various birds diversity, and the forest remaining should be well-managed to support its conservation goals.